Penggunaan Media Film Untuk Meningkatkan Minat Belajar Siswa Dalam Pembelajaran Akhlak Di Sekolah Dasar Pangkalan Kerinci - Wardi Wardi; Al Afif Hazmar; Rian Vebrianto (Journal of Innovative and Creativity, 2026)
Moral Education in Elementary Schools requires learning media that can attract students’ interest. One of the media that can be used is film, as it presents moral values in a visual and contextual manner. This study aims to examine the validity and practicality of film media in increasing students’ learning interest in Moral Education at elementary schools. This research employs a Research and Development (R&D) method using the ADDIE model, limited to the analysis, design, and development stages. The research instruments include expert validation sheets and practicality questionnaires for teachers and students. The results indicate that film media falls into the very valid category based on assessments from content and media experts, and is very practical based on responses from teachers and students. Therefore, film media is appropriate to be used in Moral Education to enhance elementary students’ learning interest.